Proceedings of the International Conference of Health Development. Covid-19 and the Role of Healthcare Workers in the Industria 2020
DOI: 10.2991/ahsr.k.201125.064
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Academic Stress During the Covid-19 Pandemic in Nursing Students of UPN Veteran Jakarta

Abstract: Background: Academic stress is one of the biggest health problems that have an impact on academic performance. Students become a group that is vulnerable to the stress that comes from academic life.Academic stress that is usually experienced by students is due to academic responsibility. The online learning system that has changed during the Covid-19 pandemic requires students to get more assignments and a busy lecture schedule. Method: This study used a cross-sectional study design. The respondents were 175 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…This percentage is lower than that found in the previous PAS instrument (Bedewy and Gabriel, 2015). The findings of this study corroborate prior research stating the same thing about academic stress in nursing students caused by online learning throughout the co-assistance program stage (Brown, Anderson-Johnson and McPherson, 2016;Rosaline and Anggraeni, 2020;Oducado and Estoque, 2021;Shetty, Kmath and Nalini, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This percentage is lower than that found in the previous PAS instrument (Bedewy and Gabriel, 2015). The findings of this study corroborate prior research stating the same thing about academic stress in nursing students caused by online learning throughout the co-assistance program stage (Brown, Anderson-Johnson and McPherson, 2016;Rosaline and Anggraeni, 2020;Oducado and Estoque, 2021;Shetty, Kmath and Nalini, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Previous research has shown that nursing students experience academic stress caused by the Covid-19 pandemic (Rosaline and Anggraeni, 2020). On the other hand, previous study did not specifically measure academic stress on students at the professional stage.…”
Section: Introductionmentioning
confidence: 95%
“…Current literature on nursing students during the pandemic has mostly come from studies conducted outside the United States (US). Globally, the pandemic caused disruptions in the lives of nursing students, resulting in physical and psychological effects that impacted academic performance ( Agu et al, 2021 ; Dewart et al, 2021 ; Dutta et al, 2021 ; Ersin & Kartal, 2020 ; Gallego-Gomez et al, 2020 ; Garcia-Gonzalez et al, 2021 ; Gaur et al, 2020 ; Gopal et al, 2021 ; Hussien et al, 2020 ; Ilankoon et al, 2020 ; Langegard et al, 2021 ; Rosaline & Anggraeni, 2021 ). Findings show the initial change to online learning was hampered by students' limited preparedness for online learning ( Dutta et al, 2021 ; Gaur et al, 2020 ; Langegard et al, 2021 ), with technological barriers (such as lack of computers and internet access) prevalent ( Agu et al, 2021 ; Gaur et al, 2020 ; Ilankoon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings show the initial change to online learning was hampered by students' limited preparedness for online learning ( Dutta et al, 2021 ; Gaur et al, 2020 ; Langegard et al, 2021 ), with technological barriers (such as lack of computers and internet access) prevalent ( Agu et al, 2021 ; Gaur et al, 2020 ; Ilankoon et al, 2020 ). Moreover, nursing students were encountering non-school concerns such as financial struggles, family responsibilities, and modified living conditions ( Gallego-Gomez et al, 2020 ; Heilferty et al, 2020 ; Rosaline & Anggraeni, 2021 ). To date, international research has focused on the effect of the pandemic on nursing students' academic performance, not on the potential impact on new nurses' entry to practice.…”
Section: Introductionmentioning
confidence: 99%
“…Hingga saat ini, penyebab pasti terjadinya PMS masih belum diketahui dengan jelas (Hasanah et al, 2020;Kusnayat et al, 2020). Tingkat stres akademik mahasiswa keperawatan lebih tinggi dibandingkan jurusan lainnya (Rosyidah, Efendi, Arfah, Jasman, & Pratami, 2020) (Rosaline & Anggraeni, 2020). Mahasiswi yang mengalami stres akademik lebih tinggi daripada mahasiswa laki-laki (Dhull & Kumari, 2015;Hafifah, Widiani, & Rahayu, 2017).…”
unclassified